Experimental Study on Dynamic Splitting Characteristics of Carbon Fiber Reinforced Concrete - Zhan-Yang Chen (Materials, 2021)
Due to the non-uniform tension and compression strength of concrete, carbon fiber can be added to concrete to improve its static tensile behavior and increase the tension–compression ratio. In view of the destructive consequences of impacts and explosions, it is necessary to study the dynamic responses of carbon fiber reinforced concrete (CFRC) structures. Therefore, the effects of the stress rates and carbon fiber contents on the dynamic tension behavior of CFRC were investigated in this paper. The dynamic splitting tests of concrete with the fiber contents of 0, 0.1, 0.2, and 0.3% were carried out by using a split Hopkinson pressure bar (SHPB) device with a diameter of 74 mm. We found that with the increase of fiber content, the static tensile strength of CFRC increases obviously, but the increased amplitude tends to decrease. The dynamic tensile strength and dynamic increase factor (DIF) both increase with the increase of stress rate, but the growth rate slows down, showing an obvious rate effect. The rate sensitivity of ordinary concrete is higher than CFRC. There are significant differences in the influence of carbon fiber on the dynamic and static strength of concrete. In the design of concrete mixing proportion, the content of carbon fiber should be appropriately selected to meet the requirements of dynamic and static mechanical properties.